Pengaruh Bauran Promosi terhadap Peningkatan Penjualan Kamar di Hotel Benua Bandung - Rahadian, Dani; Pratomo, Adithya (Bina Nusantara University, 2013)
The purpose of this research is to find out the influence of promotion mix on the increase of room sale at Hotel Benua Bandung. The results of this research are expected to be used as consideration by the hotel manager in determining the influence of promotion mix on room sale, as well as using some other variables in promotion mix. This research was based on the use of data of all promotion costs and room sales at Hotel Benua Bandung during the past five years. Data were then processed by calculating the percentage using basic regression method on SPSS program. The findings proved a positive influence of promotion mix on the increase of room sales at Hotel Benua Bandung.